A Series of Footnotes to Plato's Philosophers. Issue 2 (19th April 2018) - Cherry, Kevin M.
Abstract: In her magisterial Plato's Philosophers, Catherine Zuckert presents a radically new interpretation of Plato's dialogues. In doing so, she insists we must overcome reading them through the lens of Aristotle, whose influence has obscured the true nature of Plato's philosophy. However, in her works dealing with Aristotle's political science, Zuckert indicates several advantages of his approach to understanding politics. In this article, I explore the reasons why Zuckert finds Aristotle a problematic guide to Plato's philosophy as well as what she sees as the character and benefits of Aristotle's political theory. I conclude by suggesting a possible reconciliation between Zuckert's Aristotle and her Plato, insofar as both the Socrates whom Plato made his hero and Aristotle agree that political communities will rarely direct citizens toward virtue by means of law and that we must instead look to informal means of doing so.